KEPUTUSAN INVESTASI MILENIAL PERSPEKTIF PENGETAHUAN KEUANGAN, PERILAKU KEUANGAN DAN SIKAP KEUANGAN - Martdian Ratna Sari (Universitas Multimedia Nusantara, 2021)
Abstract - This study aims to examine the factors that influence millennial investment decisions. This study predicts that financial knowledge, financial behavior and financial attitudes of the millennial generation who tend to be independent are the considerations for millennial investment decisions. Previous studies that examined investment decision factors only focused on quantitative financial factors without paying attention to financial factors in terms of knowledge and attitude maturity in managing finances. Data from PT Kustodian Sentra Efek, the current number of millennial Indonesian investors is 51.36% in the age range of 21-40 years. Therefore, this study will examine how Financial Knowledge, Financial Behavior, and Financial Attitudes influence investment decision making for the millennial generation. 123 respondent questionnaires have been collected throughout Java by using purposive random sampling. This study finds that these three variables have a positive effect on investment decision making for the millennial generation on the island of Java. Keywords: Financial Attitude; Financial Behavior; Financial Knowledge; Investment Decision; Millennial Generation